The Effect of Rock Phosphate and Level of Inoculums on The Survivability of Aspergillus niger and Its Solubilization Ability When Pelleted With Rock Phosphate - Yudi Sastro; Donny Widianto; Irfan D Prijambada (Jurnal Ilmu Tanah dan Lingkungan, 2005)
The study is intended to examine the survival of Aspergillus niger and its phosphate solubilizing ability when pelletedwith rock phosphate. An A. niger YD 17 obtainedfrom the Laboratory of Microbiology. Faculty of Agriculture, Gadjah MadaUniversity was used. The pellet was made by mixing rock phosphate (80%) with organic matter (J 3. 9% waste of tapioca. 6% rice bran, and 1% starch) and spore of A. niger. The experimental design was the Complete Randomized Design 5x4 with 3 replicatiOns. The first factor was sources of rock phosphate (Christmas Island. Jordan, China, Ciamis, and Madura). The secondfactor was the number ofinoculums i.e. control without inoculums, 107 • J(t and J(t cfu.g·'. The colony of A. niger that formed at medium of potatoes dextrose agar (PDA) and the amount of soluble phosphorus in the Pikovskaya liquid medium were parameters. Experimental results indicated that sources of rock phosphate and the number of inoculums itif1uence the A. niger survivability and its phosphorus solubilizing ability. Rock phosphate from Ciamis gave the best support for fungus survival and rock phosphate from Christmas Island was the best substrate for phosphate solubilization. The highest soluble phosphate was achieved by ul inoculums.